Effect of Ion Vacancy Migration on Open‐Circuit Voltage of Perovskite Solar Cells. Issue 1 (12th November 2021) - Lin, Zedong
Abstract : Herein, the influence of ion vacancy migration on the open‐circuit voltage ( V oc ) of perovskite solar cells (PSCs) by computer simulation is explored. It is found that for PSCs, V oc is determined not only by the carrier recombination process, but also dominantly by the space charge effect of the ion vacancy stored within the Debye layers of the perovskite absorber layer. The migration of ion vacancy affects the ionic charge accumulation within the Debye layers, which affects the screen voltage via the space charge effect and thus determines V ocr and V ocf (open‐circuit voltage for reverse sweep and forward sweep, respectively). By tuning the parameters that determine ion vacancy mobility, the effects of ion vacancy mobility on V ocr and V ocf is investigated. Abstract : For perovskite solar cells, the open‐circuit voltage is affected dominantly by the space‐charge effect generated by the ion vacancy stored within the Debye layers of the perovskite absorber layer. The ion vacancy mobility affects the ionic charge accumulation within the Debye layers, which affects the screen voltage and thus determines the open‐circuit voltage for reverse and forward sweeps.